Implementation of the Personnel Management Information System for the Tangerang Regency Regional Civil Service Agency - Libriantono, Bambang (The International Journal of Education Management and Sociology, 2024)
The research aims to design and build a personnel database application program at the Tangerang Regency Regional Personnel Agency (BKD) using the Visual Basic 6.0 program. The data collection methods used were interviews, literature, and documentation. Once the data required to create the program is sufficient, the program creation process continues with preparing equipment and materials and designing forms and databases. The research results show that the program design consists of data entry processes, data search, and reports. To ensure data security, access rights are differentiated for each user. Apart from that, the application program is equipped with a database backup program that will duplicate the main database file into another directory. To make it easier to distribute reports, the application program is equipped with reports designed with Crystal Report 8.5, so that users just press the printer icon to print the document. The appearance of the program is quite simple but in terms of how to use the program, it needs special attention. Therefore, users need to read how to use the program which can be found in the Help file on the Installation CD. After testing, the designed program can be used to apply to the research object